Feasibility, Safety, and Efficacy of Segmental Spinal Anesthesia with Predominantly Isobaric Levobupivacaine: A Tertiary Care Hospital Study - Goyal, Lalit; Gupta, Saloni; Nagar, Sachin; Bhargava, Vinay (Faculty of Medicine Universitas Padjadjaran, 2024)
Objective: To assess feasibility, safety, and efficacy of segmental spinal anesthesia with isobaric levobupivacaine in patients undergoing various abdominal and lower limb surgeries. Methods: This was a prospective cohort study conducted at the Department of Anesthesiology and Critical Care of Kota Heart Institute and group of hospitals in India. The study involved 100 patients undergoing various abdominal and lower limb surgeries under segmental spinal anesthesia (SSA). Isobaric levobupivacaine 0.5% with fentanyl 20-25 μg or dexmedetomidine 5-10 as adjuvant or hypobaric levobupivacaine 0.167% was injected in intervertebral space depending on the surgery. Hemodynamic parameters, postoperative pain level, and adverse effects were analyzed with a p-value less than 0.05 was considered statistically significant.Results: An overall male predominance was observed with a 1:0.515 male-to-female ratio. The most affected age group was 41-50 years (37%), with a mean age of 44.51 ± 11.72 years. ASA classification indicated 34% of patients in ASA I, 40% in ASA II, 24% ASA III and 2% in ASA IV . The primary surgery was laparoscopic cholecystectomy (26%) in normal risk group and orthopedic in high-risk group(20%). Postoperative pain assessment showed mean VAS scores ranging from 1.92 to 3.42 at different time intervals. Common adverse effects were hemodynamic instability (13%), shoulder tip pain (33%), PONV (3%), headache (6%), pruritis (2%) and urinary retention (1%). The hemodynamic instability showed less incidence in ASA III/IV category.Conclusion: Segmental spinal anesthesia can be used successfully for abdominal and lower limb orthopedic surgeries in patients of ASA I to ASA IV.